EXPERIMENTAL AND THEORETICAL STUDY FOR SEALING EFFECTS OF SQUEEZ AIR FILM. - Hussain Yousif M (Journal of Engineering, 2005)
The sealing effects of squeeze air film were analyzed experimentally and theoretically The air flow rate and the sealed pressure were measured in a squeeze face seal. The air flow rate can be expressed as the difference between the flow rate by the pumping and the flow rate by the leakage. The air flow rate by the pumping increases proportionally to the square of the vibration amplitude of the surface, as does the sealed pressure. The air flow rate by the leakage increases proportionally to the pressure difference between the vessel pressure and the ambient pressure. The experimental results showed good agreement with the theoretical results.